Presentation and Outcome of Surgical Treatment of Malrotation in Children - Bhuiyan, Md Akbar Hussain; Chowdhury, Tanvir Kabir; Rahman, MA Mushfiqur; Farooq, Abdullah Al; Hoque, Md Momtazul; Sajid, Md Minhajuddin; Hakim, Md Monjurul; Banu, Tahmina (Journal of Chittagong Medical College Teachers' Association, 2012)
Introduction : Malrotation is a common anomaly in the pediatric age group which includes a wide spectrum of anomalies of Rotation. Both acute and chronic presentations are common. Atypical malrotation not having all the features of classic mal Rotation is frequently found which a diagnostic dilemma and the management varies from centre to centre. Materials and Methods : The medical records of all patients with symptomatic malrotation, who underwent surgery between July 2001 to June 2011, were retrospectively reviewed. Patients’ presentation, management, operative findings and complications were evaluated. Results : 68 patients underwent surgery for malrotation at a median age of 2 years. Male to female ratio was 2:1. 28(41%) presented with acute symptoms and 40(59%) with chronic symptoms. 54(79%) patients had vomiting, 36 (%3%) presented with abdominal distension, 19(28%) had recurrent abdominal pain. Diagnostic laparoscopy was done in 7(10%) patients. Ladd’s band was found in 16(24%) patients and Volvulus was found at the time of surgery in 5(7%) patients. 5(7%) patients also had associated anomalies. Ladd’s procedure was done in 15(22%) patients and 23(34%) patients needed resection and anastomosis. Median length of hospital stay was 10 days. Postoperative bowel obstruction was seen in 4(6%) patients and 2(3%) patients had post operative intussusceptions. There was 2(3%) death due to septicaemia with volvulus and gangrenous gut. Conclusion : The clinical presentation and anatomy of malrotation occurs along a wide clinical and anatomic variations and a high index of suspicion is required to prevent a delay in diagnosis. JCMCTA 2011; 22(2): 17-21